SOME MORPHOLOGICAL CHARACTER AND BEHAVIOR OF RED FLOUR BEETLE TRIBOLIUM CASTANEUM (COLEOPTERA: TENEBRIONIDAE - Abbas, Iman (University of Thi-Qar Journal of agricultural research, 2025)
The study of the flour beetle or dark beetle was targeted for its economic importance because of the damage it causes to dry grain crops. The study dealt with determining the length and width of the adult insects, the larva, and the pupae, so the adult was the widest (0,62) mm and the larva was the longest (2,673) mm. Also, the length of the antenna was determined and it reached (0.253) mm as well an expansion was observed in the last three segments of the antenna. The study proved that the fore and hind legs have two claws and four tarsus segments , and one claw for the middle legs with five tarsus segments. their distribution was determined in a volume of (12,5 ) cm3 of flour, so the adult was the most prevalent compared to pupae and larvae Also, the adult colors were observed and recorded, as it was dark brown, while the larvae was pale yellow, and the pupae was pale white. The type of larvae was also determined, it was protopoda, while the pupal type was obtect pupa. The adult beetle is flightless and has an affinity for light